Pengaruh Penggunaan Berbagai Jenis Sumbu Dan Media Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Keriting (Brassica Juncea L.) Varietas Samhong King Pada Hidroponik Sistem Wick - Fajari, Ilham; Syah, Bastaman; Sugiono, Darso (JURNAL AGROPLASMA, 2023)
Hydroponics is a planting system in agriculture that uses a mixture of water and nutrient solutions as a growth medium to replace the role of soil in meeting nutrient needs and uses non-soil growing media as a planting technique. Hydroponic wick system is one of the hydroponics that uses the working principle of water capillary action by using the axis as an intermediary for the rise of water from the nutrient container to the plant root area. The research method used was the experimental method using a factorial Randomized Block Design (RBD). There are 2 factors consisting of 16 treatments. The first factor is the type of wick which consists of 4 levels, namely Flannel, Wool, Stove Wick and. The second factor was the type of planting medium which consisted of 4 levels, namely Rockwool, Cocopeat, Â Hydroton and Sewdust. Each experiment was repeated 3 times so that a total of 48 experimental units were obtained. The experimental results showed that there was an interaction effect between the type of axis and the planting medium on plant height at 35 and 40 days after planting and number of leaves at 7, 14, 21 and 28 days after planting curly mustard greens (Brassica juncea L.) Samhong King variety in hydroponic wick system. In the flannel axis type, the optimal planting media type is cocopeat planting media with a fresh weight yield of 282,13 g giving the highest yield on the flannel axis type with a yield of 187,84 g.